Epidemiology of Pancreatic Cancer in Saudi Arabia: A Retrospective Analysis of Pancreatic Cancer Diagnosed in Saudi Arabia Between 2004 and 2015 - Alghamdi IG; Almadi M; Alsohaibani F; Mosli M; De Vol EB; Abaalkhail F; AlSaif FA; Al-hamoudi WK; Al-Sanea N; Hassanain M; Alqahtani SA (Clinical and Experimental Gastroenterology, 2021)
Ibrahim G Alghamdi,1 Majid Almadi,2,3 Fahad Alsohaibani,4 Mahmoud Mosli,5 Edward B De Vol,6 Faisal Abaalkhail,7,8 Faisal A AlSaif,9 Waleed K Al-hamoudi,10 Nasser Al-Sanea,11– 13 Mazen Hassanain,9,14 Saleh A Alqahtani6,15,16 1Public Health Department, College of Applied Medical Sciences, University of Al-Baha, Al-Baha, Saudi Arabia; 2Division of Gastroenterology, Department of Medicine, College of Medicine, King Khalid University Hospital, King Saud University, Riyadh, Saudi Arabia; 3Division of Gastroenterology, McGill University Health Center, Montreal General Hospital, McGill University, Montreal, Canada; 4Department of Medicine, King Faisal Specialist Hospital & Research Center, Riyadh, Saudi Arabia; 5Division of Gastroenterology, Department of Medicine, King Abdulaziz University, Jeddah, Saudi Arabia; 6Biostatistics, Epidemiology, and Scientific Computing Department, King Faisal Specialist Hospital & Research Center, Riyadh, Saudi Arabia; 7Gastroenterology Section, Department of Medicine, King Faisal Specialist Hospital and Research Center, Riyadh, Saudi Arabia; 8College of Medicine, Alfaisal University, Riyadh, Saudi Arabia; 9Department of Surgery, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 10Liver Disease Research Center, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 11Health Affairs, Princess Nourah Bint Abdulrahman University, Riyadh, Saudi Arabia; 12Department of Surgery, College of Medicine, Alfaisal University, Riyadh, Saudi Arabia; 13Department of Surgery, King Faisal Specialist Hospital & Research Center, Riyadh, Saudi Arabia; 14Department of Pediatrics, Baylor College of Medicine, Houston, TX, USA; 15Liver Transplant Center, King Faisal Specialist Hospital & Research Center, Riyadh, Saudi Arabia; 16Division of Gastroenterology and Hepatology, Johns Hopkins University, Baltimore, MD, USACorrespondence: Saleh A AlqahtaniLiver Transplant Center, King Faisal Specialist Hospital and Research Centre, Riyadh, Saudi ArabiaEmail salalqahtani@kfshrc.edu.saPurpose: Over the last decades, the incidence of pancreatic cancer has increased, particularly in countries with a higher socioeconomic status. The present work aimed to provide detailed epidemiological data on the incidence of pancreatic cancer in Saudi Arabia.Patients and Methods: In this retrospective descriptive study, the epidemiological data on pancreatic cancer cases diagnosed in 13 administrative regions of Saudi Arabia between January 2004 and December 2015 were extracted from the Saudi Cancer Registry. The frequency, the crude incidence rate (CIR), and the age-standardized incidence rate (ASIR), stratified by geographical region, gender, and the year of diagnosis, were analyzed.Results: From January 2004 to December 2015, a total of 2338 cases of pancreatic cancer were registered, including 1443 males and 895 females. The overall CIR was 1.28/100,000 among males and 0.80/100,000 in females, with an overall ASIR of 2.26 and 1.41/100,000 for males and females, respectively. Higher ASIR and CIR were observed among males than females (ratio 1.6). In both genders, the ASIR of pancreatic cancer increased with increasing age, with the highest incidence in patients aged 70 years or more. The ASIR in the Eastern Region (3.2/100,000) and the regions of Riyadh (3.0/100,000) and Tabuk (2.6/100,000) proved to be significantly higher than in the other regions of the country. Among women, the ASIR was significantly higher in Riyadh (2.3/100,000), the northern region (2.2/100,000), and Tabuk (2.0/100,000).Conclusion: This study revealed a slight increase of the CIR and ASIR of pancreatic cancer among males and females of the Saudi population. Eastern region, Riyadh, and Tabuk had the highest overall ASIRs of pancreatic cancer among males, Riyadh, Northern region, and Tabuk among Saudi females. The area least affected by pancreatic cancer was observed in Jazan among male and female Saudis. The rates of pancreatic cancer in Saudi Arabia were significantly higher among males compared with female Saudis. Further analytical studies are needed to identify the potential risk factors for pancreatic cancer among the Saudi population.Keywords: pancreatic cancer, epidemiology, Saudi Arabia, incidence, Middle-East